A spotlight on the MSc Cancer at UCL, 15 years on - Koushyar, Sarah; Hartley, John A. (Frontiers in Oncology, 2025)
Cancer remains one of the most significant global health challenges, thus education on the most recent advancements in the understanding of cancer science, diagnosis and treatment is vital. The University College London (UCL) MSc Cancer is now in its 15th year. This program not only equips students with the comprehensive knowledge of cancer biology and therapeutics but provides cutting edge skills needed to succeed beyond the MSc. The curriculum integrates the fundamentals of normal cell and cancer biology through to the cancer patient, creating a bench to bedside educational pipeline. This article gives a holistic overview of the MSc Cancer curriculum, the research-led educational practices being carried out, the research opportunities that branch from this MSc and the career prospects of MSc Cancer graduates. Further detailed information on the MSc Cancer can be found here: Cancer MSc | Prospective Students Graduate - UCL – University College London.